Coxsackievirus Type B3 Is a Potent Oncolytic Virus against KRAS-Mutant Lung Adenocarcinoma - Haoyu Deng; Huitao Liu; Tanya de Silva; YuanChao Xue; Yasir Mohamud; Chen Seng Ng; Junyan Qu; Jingchun Zhang; William W.G. Jia; William W. Lockwood; Honglin Luo (Molecular Therapy: Oncolytics, 2019)
KRAS mutant (KRASmut) lung adenocarcinoma is a refractory cancer without available targeted therapy. The current study explored the possibility to develop coxsackievirus type B3 (CVB3) as an oncolytic agent for the treatment of KRASmut lung adenocarcinoma. In cultured cells, we discovered that CVB3 selectively infects and lyses KRASmut lung adenocarcinoma cells (A549, H2030, and H23), while sparing normal lung epithelial cells (primary, BEAS2B, HPL1D, and 1HAEo) and EGFRmut lung adenocarcinoma cells (HCC4006, PC9, H3255, and H1975). Using stable cells expressing a single driver mutation of either KRASG12V or EGFRL858R in normal lung epithelial cells (HPL1D), we further showed that CVB3 specifically kills HPL1D-KRASG12V cells with minimal harm to HPL1D-EGFRL858R and control cells. Mechanistically, we demonstrated that aberrant activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and compromised type I interferon immune response in KRASmut lung adenocarcinoma cells serve as key factors contributing to the sensitivity to CVB3-induced cytotoxicity. Lastly, we conducted in vivo xenograft studies using two immunocompromised mouse models. Our results revealed that intratumoral injection of CVB3 results in a marked tumor regression of KRASmut lung adenocarcinoma in both non-obese diabetic (NOD) severe combined immunodeficiency (SCID) gamma (NSG) and NOD-SCID xenograft models. Together, our findings suggest that CVB3 is an excellent candidate to be further developed as a targeted therapy for KRASmut lung adenocarcinoma. Keywords: coxsackievirus B3, oncolytic virus, lung adenocarcinoma, KRAS mutation, EGFR mutation, ERK1/2 signaling, type I interferon, enterovirus, virotherapy